Selective β2‐adrenoreceptor signaling regulates osteoclastogenesis via modulating RANKL production and neuropeptides expression in osteocytic MLO‐Y4 cells. Issue 5 (1st November 2018) - Liang, Hengxing; Zeng, Yuanyuan; Feng, Yunzhi; Wu, Hanjiang; Gong, Ping; Yao, Qianqian
Abstract: The β2‐adrenergic receptor (β2‐AR) signaling on bone cells is the major contributor in the effect of the sympathetic nervous system on bone turnover. However, it remains unclear whether receptor activator of nuclear factor κ‐Β ligand (RANKL) modulation and neuropeptides expression in osteocytes are responsible for the mechanism. This study used β2‐AR stimulation to investigate cell cycle and proliferation, the gene and protein expression of RANKL, and osteoprotegerin (OPG), as well as neuropeptides regulation in osteocytic MLO‐Y4 cells. Clenbuterol (CLE; a β2‐AR agonist) slightly promoted the growth of MLO‐Y4 cells in a concentration‐dependent effect but had no effect on the proliferation index. And the concentration of 10 −8  M showed a significant increase in the S‐phase fraction on day 3 in comparison with the control. Additionally, CLE‐promoted osteoclast formation and bone resorption in osteocytic MLO‐Y4 cell‐RAW264.7 cell cocultures. RANKL expression level and the ratio of RANKL to OPG in MLO‐Y4 cells were enhanced in CLE treatment but were rescued by blocking β2‐AR signaling. However, neuropeptide Y and α‐calcitonin gene‐related peptide, two neurogenic markers, were inhibited in CLE treatment of MLO‐Y4 cells, which was reversed by a β2‐AR blocker. The results indicate that osteocytic β2‐AR plays an important role in the regulation of RANKL/OPG and neuropeptides expression, and β2‐AR signaling in osteocytes can be used as a new valuable target for osteoclast‐related pathologic disease. Abstract : 1. Cell activity and the ratio of receptor activator of nuclear factor κ‐Β ligand (RANKL) to osteoprotegerin (OPG) on MLO‐Y4 cells are mediated through selective β2‐adrenergic signaling modulation. 2. The β2‐AR agonist clenbuterol (CLE) stimulate osteoclasts and bone resorption pits formation on MLO‐Y4 cell‐RAW264.7 cell cocultures via RANKL/OPG modulation in osteocytic MLO‐Y4 cells, whereas it was rescued by blocking β2‐AR signaling. 3. Neuropeptide Y and α‐calcitonin gene‐related peptide, two neurogenic markers, were inhibited in CLE treatment of MLO‐Y4 cells, which was reversed by a β2‐AR blocker.